PENDUDUK DAN AKSES AIR BERSIH DI KOTA SEMARANG - Fadjri Alihar (Jurnal Kependudukan Indonesia, 2018)
Semarang is a metropolitan city located in the northern coast of Java Island with about 1.7 million inhabitants. This city encounters two problems concerning with water, namely rob floods and clean water availability. This paper aims to study about access of the population to clean water and the issues faced by the community related to its availability. This study used data from the research conducted by Urban Human Ecology research group, Research Center for Population - LIPI in 2012. This study applied a qualitative approach through interviews and focussed group discussions (FGDs). The results show that people who live in areas that are often hit by rob floods cannot access clean water and have to buy it to fulfil their household needs. Another problem faced in the city is undrinkable groundwater due to environmental degradation and seawater intrusion. On the other side, the regional water company (PDAM) in this city has not been able to serve clean and drinkable water for the entire area of Semarang due to its limited service network. In order to meet the need of water, it is recommended to strengthen the company capabilities through human capital development as well as an expansion of clean water networks in the city